McNally's gamble - Sanders, Lawrence, 1920- (G.P. Putnam's Sons, 1997)
When not wining, dining, or driving his fire-engine red Miata around Palm Beach, Archy keeps discreet tabs on the wealthy clients of his father's law firm. Then one day, Edythe Westmore, a well-to-do widow, considers buying a Faberg ̌Imperial Egg and all hell breaks loose.